Level of physical activity among students from universities in Wrocław - Barbara Grabowska (Medycyna Ogólna i Nauki o Zdrowiu, 2020)
Introduction and Objective Physical activity is an essential and integrating component of a health-promoting lifestyle. The aim of the study was assessment of the level of physical activity of students according to the type of university, gender and place of residence.